A Generic Power Flow Algorithm for Unbalanced Islanded Hybrid AC/DC Microgrids - Pompodakis, Evangelos E.; Kryonidis, Georgios C.; Demoulias, Charis; Alexiadis, Minas C. (IEEE transactions on power systems, 2021)
This paper proposes a precise power flow algorithm for islanded hybrid AC/DC microgrids (HMGs). In our analysis, we have considered a multi-grounded unbalanced bipolar DC microgrid and a multi-grounded four-wire AC microgrid connected through one or more interlinking converters (ICs). The proposed method is based on the implicit Z BUS method, presenting fast convergence and robustness regardless of the R / X ratio of the lines. It can be applied in all network configurations including highly meshed distribution systems. Numerical simulations are conducted in a 12-Bus and a 47-Bus islanded unbalanced HMG to verify the validity of the proposed power flow approach considering several distributed generator (DG) operational modes. A case study in a large 1024-Bus islanded HMG further highlights the outstanding accuracy and computational performance of the proposed approach against other existing power flow methods.